Motivators for University of Professional Studies Accra Students to Adopt a Learning Management System in Ghana - Attuquayefio Samuel NiiBoi (De Gruyter, 2023)
The use of a learning management system (LMS) is believed to be significant for students' academic performance, but students' attitudes regarding its use are divided. Therefore, the purpose of this study is to apply a modified version of the technology acceptance model to determine the motivators for University of Professional Studies Accra students' behavioural intentions (BIs) and actual use of LMSs using a convenient sampling technique to elicit data from first-year students in the faculty of information technology and communication studies. The investigation included a total of 188 samples. The study used structured equation modelling partial least squares to analyse the data. Specifically, the study employed the importance-performance map analysis to establish the factors that are important to students' actual use of an LMS. The study's findings suggest that REL and output quality significantly impact the perceived usefulness (PU). Also, perceived enjoyment and subjective norm exert a significant impact on the perceived ease of use (PEOU). Additionally, PEOU influences the PU, which in turn influences the BI. Furthermore, the findings reveal a strong link between BI and the actual use of the LMS. Finally, the study suggests that students' BI to use the LMS is the most important factor for students' actual use. PU is also an important determinant factor of students' actual use. Following the study's conclusion that BI and PU are important for students' actual use of an LMS, higher education administrators must develop rules that increase the students' PU of LMSs, while also ensuring that current measures that awaken students' BIs are maintained or improved so that students can use the LMS for academic work.